An investigation of pedigree dog breeding and ownership in the UK: experiences and opinions of veterinary surgeons, pedigree dog breeders and dog owners - Kuhl, C. (2017)
Pedigree dog welfare in the United Kingdom is a controversial subject. This PhD aimed to investigate small animal veterinary surgeons’ (VS), pedigree dog breeders’ (PDB) and owners’ perceptions surrounding canine health, their roles, information acquisition and the quality of online resources available to new dog owners. Via a mixed-methods approach VS and PDB were asked about their perceptions of pedigree dog welfare using online questionnaires. Focus groups were then used to explore these parties’ opinions on advising dog owners and buyers. Dog owners were administered an online questionnaire to explore drivers of dog acquisition and sourcing of information about canine health. A further sample of dog owners provided possible internet search terms they would use to find information on how to care for a new dog. These terms were used for a scoping review to examine the quality of available information. The VS and PDB exhibited varied perceptions relating to pedigree dog breeding, inherited disease and health screening programmes. Each group considered themselves the most knowledgeable on these topics and lacked clarity on how their roles interrelated. Focus groups showed conflicting views on advising dog owners and buyers. Dog owners varied in their drivers for ownership, from whom they obtained information and the internet search terms used when looking for information online. The scoping review identified a lot of easy to understand, poor quality information. VS and PDB need to better understand and appreciate each others’ roles, perspectives and knowledge to instigate effective collaboration and improve pedigree dog health. Owners are diverse and require a multifaceted educational approach to improve knowledge. The quality of online information for owners needs to be made clear and a coordinated approach involving all stakeholders is required to enable dissemination of practical, evidence-based information on pedigree dog health.